Infrared thermography in clinical practice: a literature review - Qian Liu; Mingzhu Li; Wenping Wang; Shengbo Jin; Haozhe Piao; Yuxin Jiang; Ningxin Li; Huini Yao (European Journal of Medical Research)
Abstract Background Infrared thermography technology is a diagnostic imaging modality that converts temperature information on the surface of the human body into visualised thermograms. This technology has the capacity to intuitively detect the presence of certain abnormal conditions or foci in the human body. In recent years, the application of this technology in medicine has become increasingly extensive, especially in the areas of auxiliary diagnosis and early screening of diseases. Objectives The aim of this review is to analyse and summarise the application of infrared thermography in clinical practice. Methods A comprehensive search of the research literature pertaining to the clinical application of medical infrared thermography was conducted, encompassing publications by both domestic and foreign researchers and scholars, in prominent databases including PubMed, ISI Web of Science, and CNKI since the inception of these databases. Results A total of 51 articles were ultimately included in the study. The application of infrared thermography has been demonstrated in oncology, painful diseases, inflammation, rheumatism, and vascular-related diseases. Conclusions The extensive utilisation of infrared thermography in clinical settings signifies the technology’s considerable potential. Addressing its current limitations can optimise its benefits.